The Effect Of Using Online Technology On Quality Of Services For Opening Accounts In BCA Bank Surabaya - Novaquita Novaquita (Journal of World Conference (JWC), 2019)
This study aims to analyze the effect of perceived usefulness, perceived ease of use, convenience, and security have a simultaneous and partial effect on quality online technology usage services for customers in opening accounts at BCA Bank Surabaya .The method used by the author is a quantitative method with an approach analytical descriptive. The research variable used is TAM (Technology Acceptance Model). The research results show that Perceived Usefulness (X1), Perceived Ease of Use (X2), Comfort (X3), and Security (X4), affect simultaneously to dependent variable Service Quality (Y). Thus the first hypothesis is states "That Perceived Usefulness, Perceived Ease of Use, Comfort, and Simultaneous influential security of service quality "is empirically proven the truth. While partially, perceived ease of use, security, and comfort, no significant effect on service quality, only perceived usefulness variables only that has a significant effect on service quality variables. Research results too shows that the perceived usefulness variable is the dominant variable affect the quality of service at the opening of an online account system at the bank BCA.